A survey on peer-to-peer energy trading for local communities: Challenges, applications, and enabling technologies - Nadeem, Adnan (Frontiers in Computer Science, 2022)
Electricity is still a highly demanding resource in developing countries specifically their rural areas. Local communities in developing countries are now focusing on generating their own electricity using solar and trading the energy which is in access to the supplier. Energy trading at the peer-to-peer level is a novel paradigm. It allows customers to contribute energy to the grid and power generation and supply companies. In this paper, we investigate the energy trading enabling technologies, their applications, challenges, and benefits to the local communities from various aspects. We will analyze how blockchain and IoT technologies can help energy trading at the customer level from recent research proposals. We will also present our analysis of recent research, its implementation of energy trading technologies, and future directions.